Implementasi Undang-Undang No. 6 Tahun 2014 tentang Desa Terkait Pelaksanaan Tugas Kepala Desa dalam Penyelesaian Perkara Masyarakat Desa (Studi Kasus Pada Desa Ngadiluwih) - Ningsih, Tri Rahayu; Purimaharani, Andina Elok (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2022)
The aims of this research are to find out and analyzehow the role of the village head in resolving communitydisputes in the village related to the implementationof Law Number 6 year 2014 on Villages, whichoccurred in Ngadiluwih Village, Matesih Subdistrict, Karanganyar Regency. In addition, italso aims to examine the factors inhibiting the role ofngadiluwih’s village head in the process of resolvingcommunity disputes in the village. This research is atype of empirical juridical research with descriptiveproperties and using a case approach. Data iscollected through interviews and documentation.The data is analyzed by inductive methods whosesteps include data reduction, data calcification, datasystematization and finally conclusion making. Theresults of this study showed the first task of the villagehead related to the implementation of Law No. 6 year2014 on Villages related to the role of village headsin the dispute resolution process in NgadiluwihVillage that has been implemented but not optimally.These two studies show obstacles in implementing theduties of the village head in the process of resolvingdisputes between Ngadiluwih villagers.